2020
DOI: 10.3389/fpsyg.2020.02259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an 8-Week Yoga-Based Lifestyle Intervention on Psycho-Neuro-Immune Axis, Disease Activity, and Perceived Quality of Life in Rheumatoid Arthritis Patients: A Randomized Controlled Trial

Abstract: Various external stressors and environmental challenges lead to the provocation of the immune system in autoimmune diseases like Rheumatoid arthritis (RA). The inappropriate immune response further triggers the cascade of inflammatory changes resulting in precipitation of symptoms and hampers quality of life (QOL). The underlying psycho-somatic component of the disease requires a holistic approach to its treatment dimension rather than the use of pharmacotherapy. The applicability of mind-body interventions ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 63 publications
3
82
0
Order By: Relevance
“…Yoga has been found useful in autoimmune conditions such as rheumatoid arthritis. Studies indicate the usefulness of Yoga in reducing the serological markers of inflammation along with symptoms, both physical and psychological, when Yoga is administered along with medications [ [14] , [15] , [16] ]. A Cochrane review indicated positive outcomes of Yoga in patients with chronic pain [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yoga has been found useful in autoimmune conditions such as rheumatoid arthritis. Studies indicate the usefulness of Yoga in reducing the serological markers of inflammation along with symptoms, both physical and psychological, when Yoga is administered along with medications [ [14] , [15] , [16] ]. A Cochrane review indicated positive outcomes of Yoga in patients with chronic pain [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced levels of MCP-1 have chemotactic activity on monocytes, enhance the T cells activity (Carr et al, 1994), and stimulate transforming growth factor-β and collagen synthesis (Gharaee-Kermani et al, 1996;Hogaboam et al, 1999). In rheumatoid arthritis, Yoga affects the psycho-neuro-immune axis by reduction in inflammatory cytokines and improvement in mind-body communicative markers and quality of life; disease activity was also reduced in yoga group (Gautam et al, 2020).…”
Section: Yogic Breathing On Stress Levels and Immunitymentioning
confidence: 99%
“…It works through many mechanisms and has been associated with many positive and objectively measurable changes in an individual, which include reducing stress and anxiety, warding off depression, improving sleep, reducing sympathetic distress, reducing hypertension symptoms, decreasing inflammation, and improving the quality of life. 8,13,14,[16][17][18] The relaxation response elicited due to yoga leads to an elevation of β-endorphins, improvement in cardiovagal tone, reducing sympathetic overactivity, lowering of IOP, and reduces further damage to RGCs. 12,19,20 Yoga is also known to enhance cognitive abilities, boosting memory, increasing thickness of cerebral cortex, neural connectivity, positive changes in electroencephalogram (EEG), and improving neuroplasticity.…”
Section: Manuscriptmentioning
confidence: 99%
“…21,22,23 Our recent randomized controlled trial (RCT) on the impact of yoga on RA patients published in Frontiers in Psychology, 2020 supports yoga as an adjunctive therapy to treat this chronic progressive debilitating disease as it aids in decreasing systemic inflammation by its beneficial effects on the psychoneuro-immune axis and normalization of dysregulated transcripts (IL-6, TNF-α, NFKB1, TGF-β, and CTLA4). 8 Yoga improves the mitochondrial integrity by altering the expression levels of transcripts that maintain mitochondrial integrity, which aids in the maintenance of optimal free radical levels, holds the key to increase the mitochondrial copy number, improves COX-II activity, increases NAD+ levels, optimizes OS markers, and increases the expression levels of transcripts that maintain mitochondrial integrity, reduces disease activity and its associated consequences on physical and mental health,and hence can be beneficial as an adjunct therapy. 4,22,23 The regulation of cellular OS within physiological limits after YBLI suggests the potential of this intervention in protecting cells from OS-induced nuclear and mt DNA damage and telomere attrition and in reversing epigenetic changes, which accumulate due to unhealthy lifestyle and adverse environmental conditions.…”
Section: Manuscriptmentioning
confidence: 99%